Pulmonary vascular resistance predicts mortality in patients with pulmonary hypertension associated with interstitial lung disease: results from the COMPERA registry - Olsson, Karen Maria; Hoeper, Marius M.; Pausch, Christine; Grünig, Ekkehard; Huscher, Doerte; Pittrow, David; Rosenkranz, Stephan; Gall, Henning (The European respiratory journal, 2021)
Tweetable abstract ERSpublications - click to tweetIn patients with pulmonary hypertension associated with interstitial lung disease, pulmonary vascular resistance provides stronger prognostic information than mean pulmonary arterial pressure https://bit.ly/3w1QcIS
Gesehen am 26.10.2021